JOM: The Journal 2025-2026 Editorial Calendar Is Open for Submissions - Kelly Markel (JOM, 2024)
Osteopathic manipulative treatment (OMT) utilizes manual techniques to address somatic dysfunctions (SDs) and promote physiologic function. Although SDs commonly develop following traumatic injury, the role of OMT in postinjury remains incompletely characterized. Patients recovering from trauma frequently experience persistent pain and functional limitations requiring ongoing healthcare utilization. To address this need, we established a novel OMT for trauma program (OTP) to complement interventions for patients with subacute and chronic postinjury pain and mobility impairments. This study aims to evaluate the growth and effectiveness of the novel OTP over its first 3 years. We retrospectively analyzed data for all patients treated at the OTP between January 1, 2021 and December 31, 2023. The outcomes included patient volume, relative value units (RVUs), and referral patterns as well as changes in pain, mobility, and other subjective improvement patients attributed to OMT. We performed subgroup analyses of patients who reported a mechanism of injury (MOI, "Injured") and those who did not ("No MOI"). Data are presented as percentages or medians (interquartile range [IQR]). During its first 3 years, the OTP provided 279 OMT sessions for 95 patients (41 [43.16 %] male and 54 [56.84 %] female; median 52 [41.50-64.50] years-old), applying a trauma-informed biomechanical OMT model. Quarterly patient encounters, RVUs generated, and new patient referrals increased per calendar-year quarter (CYQ; r=0.74, 0.62 and 0.56 with p=0.0028, 0.028, and 0.016, respectively). Referral patterns shifted from trauma/acute care surgery (T/ACS) and Physical Medicine and Rehabilitation (PM&R; 51.85 to 25.0 % and 33.33 to 2.78 %) toward OTP patient referrals and Primary Care referrals (0-19.44 % and 11.11-47.22 %). Median pain scores decreased immediately following the first OMT session (3 [2-5] on a 10-point pain scale). OTP patients whose first follow-up was within the study period (61, 64.21 %) reported a similar decrease between OMT sessions #1 and #2 (4 [3-6]). All patients reported improved mobility immediately after OMT. Additional benefits that patients attributed to the OTP included improvements in daily activity level (75.41 %), mood (60.66 %), sleep quality (36.07 %), and pain-free periods (36.07 %). The rate of immediate post-OMT complications (universally described as musculoskeletal discomfort or pain) was 2.87 %. We detected no significant differences during subgroup analyses. Median pain scores improved similarly between Injured and No MOI subgroups immediately after OMT session #1 (3 [2-5] vs. 3.5 [1.5-4.25], p=0.337) and between OMT sessions #1 and 2 (4 [3-6] vs. 4 [1.5-6], p=0.363). Our data demonstrate that not only is it possible to integrate a novel OTP into a level 1 trauma center but also that such a program is likely to grow significantly over time and consistently provide potentially beneficial OMT services for patients who do and do not identify a MOI. Programs like the OTP may provide a distinct modality to help improve postinjury pain and mobility limitations, among other potential benefits, although further analysis is necessary to assess causality. The present data informed updates to OTP operations, including the implementation of prospective, higher-fidelity data collection to enable more detailed and accurate analyses. Further research, including comparative studies, is warranted to explore the potential benefits of OMT for the trauma population.